Investigation of physico-chemical and catalytic properties of the coating layer of silica-coated iron oxide magnetic nanoparticles. (June 2021) - Lazzarini, A.; Colaiezzi, R.; Passacantando, M.; D'Orazio, F.; Arrizza, L.; Ferella, F.; Crucianelli, M.
Abstract: Silica-coated iron oxide magnetic nanoparticles to be employed as the starting core for easily-recoverable heterogeneous catalysts supports, were synthesized. We tuned both the properties of the magnetic core and of the covering shell, with particular emphasis on the optimization of the silica layer thickness. Afterwards, structural-sensitive techniques (XRD, BET surface area analysis), surface-sensitive techniques (ATR-IR, XPS), imaging (SEM, TEM), elemental analyses (ICP-MS) and magnetization analyses (AGFM), were employed to unravel the features of the synthesized materials. The oxidation of cis -cyclooctene with tert -butyl hydroperoxide in presence of MNPs was used as probe reaction to check the reactivity of the NPs and the effectiveness of the silica shield. The results of these tests showed its chemical inertia confirming the absence of any detrimental iron oxide catalyzed side-reactions or magnetic core modification. Graphical abstract: Image 1 Highlights: Novel magnetically-recoverable catalyst supports were successfully synthesized. Physico-chemical characterization unravelled the features of these materials. Oxidation reactions confirmed the shielding properties of the silica coating.